2019
DOI: 10.1136/bmjopen-2018-023879
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to inorganic particles during pregnancy and birth outcomes: a nationwide cohort study in Sweden

Abstract: ObjectivesThe aim of this study was to investigate if occupational exposure to inorganic particles or welding fumes during pregnancy is associated with negative birth outcomes.DesignA prospective national cohort study.SettingAll single births from 1994 to 2012 in Sweden. Information on birth weight, preterm birth, small for gestational age, smoking habits, nationality, age, occupation, absence from work and education was obtained from nationwide registers. Exposure to inorganic particles (mg/m3) was assessed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
(30 reference statements)
1
14
0
1
Order By: Relevance
“…Several studies have already shown that maternal exposure to ultrafine particles in ambient air pollution is associated with adverse reproductive outcomes such as being born preterm, being small for gestational age, and fetal demise . Fewer studies exist on the association between occupational exposure to particles and adverse pregnancy outcomes, despite the fact that pollutant concentration in the workplace can be significantly higher than that of the outdoor environment …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have already shown that maternal exposure to ultrafine particles in ambient air pollution is associated with adverse reproductive outcomes such as being born preterm, being small for gestational age, and fetal demise . Fewer studies exist on the association between occupational exposure to particles and adverse pregnancy outcomes, despite the fact that pollutant concentration in the workplace can be significantly higher than that of the outdoor environment …”
Section: Discussionmentioning
confidence: 99%
“…[50][51][52] Fewer studies exist on the association between occupational exposure to particles and adverse pregnancy outcomes, despite the fact that pollutant concentration in the workplace can be significantly higher than that of the outdoor environment. 53 Nanoparticles can directly affect fetal development by crossing the placental barrier and inducing oxidative stress and inflammation in F I G U R E 6 Significant production of IL-6 and IL-8 was observed in cells exposed to GMAW-MS. the fetus. 54,55 They can also indirectly harm the developing fetus as a result of maternal inflammation caused by nanoparticle exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Fetal Air Pollution Exposure cohort was formed by merging multiple Swedish national registers, and contains information regarding all registered births between 1994 and 2014 (n=2 113 336). 22 The Medical Birth Register has a 98%–99% coverage and contains data regarding, for example, maternal age, height, weight, occupation, smoking habits, parity and country of birth, which is collected at the first visit to the prenatal care clinics (usually around gestational week 10). 23 The register also has information on diagnoses during pregnancy.…”
Section: Methodsmentioning
confidence: 99%
“…Exposure to combustion particles was also based on measurements from different work places, and was in this study expressed as yes/no based on exposure to asphalt, diesel, polycyclic aromatic hydrocarbons, lead and/or other combustion particles. 22 For job strain and physically strenuous work, an index with scores from 1 to 6 and 1-10, respectively, was calculated based on answers from the work environment survey performed by the Swedish Work Environment Authority every other year. 14 The survey is sent to a sample of the working population (ages 16-74, n≈4000-12 000) and includes questions regarding control and demands (job strain), as well as turning, lifting, bending, heavy breathing, working with hands above the head or with heavy objects, and repeated movements (physically strenuous work).…”
Section: Covariatesmentioning
confidence: 99%